Cation interdiffusion in uranium–plutonium mixed oxide fuels: Where are we now? - Vauchy, Romain; Hirooka, Shun; Matsumoto, Taku; Kato, Masato (Frontiers in Nuclear Engineering, 2022)
The diffusion phenomena in uranium–plutonium mixed oxides (U1−yPuyO2) dictate the physicochemical properties of mixed oxides (MOX) nuclear fuel throughout manufacturing, irradiation, and storage. More precisely, it is paramount to estimate the cation interdiffusion insofar as it dovetails with the actinide redistribution during sintering and under irradiation. This paper draws a critical review of the existing experimental data of U and Pu interdiffusion coefficients in MOX fuel.